The correlation between strength and power measures with sprint freestyle performance in Division 1 collegiate swimmers. Manuscript and coaching applications - Kao, S. H.; Ishida, A.; Ainsworth, B. E. (Journal of Swimming Research, 2018)
The purpose of this study was to investigate the relationship between dryland strength and power measures with sprint freestyle performance in Division 1 collegiate swimmers. Ten males (Age, M = 20.1 yrs., SD = 2.2) and eight females (Age, M = 19.4 yrs., SD = 1.3) with an average of 12.4 years of competitive swimming experience participated in the study. Dryland measures were a one-repetition maximum (1-RM) weighted pull-up test in kilograms, a non-countermovement jump (NCMJ) in centimeters, and a barbell back squat velocity test in meters per second designed to test upper body and leg strength and power. The swim task was a maximal-effort 45.72-meter freestyle swim. To normalize the data, Z-scores were computed for each variable and for the sum of the three-dryland tests. The data were analyzed using Pearson product-moment correlation analysis. In males, an inverse association was observed between the sum of the three-dryland performances and the sprint swim time (r = -0.77, p < 0.05). In females, correlations were significant between the sum of the three-dryland performances, the weighted pull-up, the back squat velocity, and the NCMJ height with the sprint swim time (r = -0.86, r = -0.66, r = -0.67, r = -0.75; p < 0.05, respectively. The results showed the importance of dryland strength and power in male and female competitive swimmers for successful sprint swimming performance.